Efektivitas Workshop Tenaga Pendidik dalam Peningkatan Mutu Guru MA Al-Amiriyah - Milati, Azka 'Afifatul; Saadah, Dewi Atiatus; Hasanah, Uswatun; Husain, Muhammad (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study analyzes the effectiveness of educator workshops in improving teacher quality at MA Al-Amiriyah, while identifying key success factors and challenges. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. Findings reveal a significant improvement in teachers’ pedagogical and professional competencies after the workshops, particularly in student-centered learning and constructive feedback. A total of 46.7% and 60% of teachers reported improvements in these areas. Teacher development also positively impacted student achievement, with average score increases ranging from 7.4% to 8.3% across subjects. This study provides empirical evidence that workshops are an effective strategy for teacher professional development in madrasas. It also offers practical recommendations for school management and training providers to design more targeted and sustainable programs. Penelitian ini bertujuan untuk menganalisis efektivitas workshop tenaga pendidik dalam meningkatkan mutu guru di MA Al-Amiriyah, serta mengidentifikasi faktor keberhasilan dan tantangannya. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan analisis dokumen. Hasil menunjukkan adanya peningkatan signifikan dalam kompetensi pedagogik dan profesional guru pasca-workshop, terlihat dari penerapan pembelajaran berpusat pada siswa dan pemberian umpan balik konstruktif. Sebanyak 46,7% dan 60% guru melaporkan peningkatan pada aspek tersebut. Peningkatan kualitas guru ini turut berdampak pada hasil belajar siswa, dengan kenaikan nilai rata-rata sebesar 7,4% hingga 8,3% di berbagai mata pelajaran. Temuan ini memberikan bukti empiris bahwa workshop merupakan strategi efektif dalam pengembangan profesional guru di madrasah. Studi ini juga menyajikan rekomendasi praktis bagi pengelola madrasah dan penyelenggara pelatihan untuk menyusun program yang lebih terarah dan berkelanjutan.